2014
DOI: 10.1186/1423-0127-21-49
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin induces MUC8 and MUC5B expression via p38 MAPK/ROS/NF-κB in human airway epithelial cells

Abstract: BackgroundAmong a variety of inflammatory mediators, visfatin is a proinflammatory adipocytokine associated with inflammatory reactions in obesity, metabolic syndrome, chronic inflammatory disease, and autoimmune disease. However, the biological role of visfatin in secretion of major mucins in human airway epithelial cells has not been reported. Therefore, this study was conducted in order to investigate the effect and the brief signaling pathway of visfatin on MUC8 and MUC5B expression in human airway epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It is well known that NAMPT treatment activates various signalling pathways, including PRKA, AKT1, MAPK3/1 and MAPK14, in different cell types (Cheng et al 2011, Brandauer et al 2013, Reverchon et al 2013a, Song et al 2014. We showed that in hen granulosa cells from F1 hierarchical follicles, NAMPT treatment decreased MAPK3/1 phosphorylation after 30 or 60 min of stimulation (Fig.…”
Section: Signalling Pathways Involved In the Nampt Effects In Hen Gramentioning
confidence: 51%
“…It is well known that NAMPT treatment activates various signalling pathways, including PRKA, AKT1, MAPK3/1 and MAPK14, in different cell types (Cheng et al 2011, Brandauer et al 2013, Reverchon et al 2013a, Song et al 2014. We showed that in hen granulosa cells from F1 hierarchical follicles, NAMPT treatment decreased MAPK3/1 phosphorylation after 30 or 60 min of stimulation (Fig.…”
Section: Signalling Pathways Involved In the Nampt Effects In Hen Gramentioning
confidence: 51%
“…Not surprisingly, many immune stimulants were found to increase MUC5B expression including visfatin (proinflammatory adipocytokine) [309], lipopolysaccharide [310], IL-13 [311], adenosine monophosphate-activated protein kinase [312], monocyte chemotactic protein 1 [313], IL-8 [314], prostaglandin [315], and staphylococcus enterotoxin A [316].…”
Section: Introductionmentioning
confidence: 99%
“…The components of this pathway that have been specifically implicated in MUC5B regulation include p38 MAPK, ERK, NF-κB, MMP-9, ROS, RSK1, CREB, IL-1β, and IL-17A [157,305,309,312,[315][316][317][319][320][321]. This pathway is undoubtedly contributing to the regulation/dysregulation of MUC5B, likely acting through a proximal promoter [322].…”
Section: Introductionmentioning
confidence: 99%
“…The NF-κB agonist LPS (10 μg/mL) and inhibitor PDTC (10 μM) were used to activate or suppress NF-κB in ATO-treated cells. Previous studies showed that LPS and PDTC at these two dosages can sufficiently activate or inhibit NF-κB without affecting cell growth in many cell lines, including HepG2 cells (Jeong et al, 2014;Song et al, 2014). The result demonstrated that ATO dosedependently decreased cell viability (Fig.…”
Section: Parp-1 Inhibitor 4an Sensitized Ato In Hepg2 Cells and Thismentioning
confidence: 75%